The Effect of Cognitive Behavioral Therapy on Depression, Anxiety, and Stress in Patients With COVID-19: A Randomized Controlled Trial - Li, Jinzhi; Li, Xiuchuan; Jiang, Jie; Xu, Xuexue; Wu, Jing; Xu, Yuanyuan; Lin, Xin; Hall, John; Xu, Huashan; Xu, Jincheng; Xu, Xiaoyue (Frontiers in Psychiatry, 2020)
Objectives: This study examined the effectiveness of Cognitive Behavioural Therapy (CBT) in relieving patients' psychological distress during the COVID-19 epidemic. Methods: Ninety-three eligible participants selected by cluster sampling were randomized to an intervention group (N=47) and a control group (N=46). Participants in the control group received routine treatment according to the Chinese Management Guidelines for COVID-19, while participants in the intervention group received routine treatment with additional CBT. The Chinese Version of Depression Anxiety and Stress Scale-21 (DASS-21) was used to evaluate depression, anxiety and stress for all participants at baseline and post-intervention. Two-sided t-test, and proportion tests were used to examine the differences between the intervention and control group for each DASS-21 indicator. Univariate linear regression was used to examine the association between chronic disease status and change in each DASS-21 indicator after intervention. Two-way scatter plots were generated to show the association of the length of hospital stay and the changes of each DASS-21 indicator by intervention and control groups. Results: Significant decreases in means were found for scales of depression, anxiety, stress and total DASS-21 in both intervention (p<0.001) and control group (p=0.001), with participants in the intervention group having a bigger reduction in means. After the intervention, more participants in the intervention group had no depression or anxiety symptoms than in the control group, but no statistical differences were found (p>0.05). Compared with participants with chronic disease, participants with no chronic disease had a significantly larger reduction of total DASS-21 scale (coefficient= -4.74, 95% CI: -9.31; -0.17).The length of hospital stay was significantly associated with a greater increase in anxiety scale in the intervention group (p=0.005), whilst no significant association was found in the control group (p=0.29). Conclusions: The patients with COVID-19 experienced high levels of anxiety, depression and stress. Our study result highlights the effectiveness of CBT in improving the psychological health among patients with COVID-19, also suggests that CBT should be focused on patients with chronic disease and those who have longer hospital stays. These results have important implications in clinical practice in improving psychological health in the context of COVID-19 pandemic.